Mild Phenotype of Arthrogryposis, Renal Dysfunction, and Cholestasis Syndrome 1 Caused by a Novel VPS33B Variant - Linhares, Natália Duarte; Fagundes, Eleonora Druve Tavares; Ferreira, Alexandre Rodrigues; Queiroz, Thaís Costa Nascentes; da Silva, Luiz Roberto; Pena, Sergio D. J. (Frontiers in Genetics, 2022)
The arthrogryposis, renal dysfunction and cholestasis syndrome (ARCS) is an autosomal recessive multisystem disease caused by variants in VPS33B or VIPAS39. The classical presentation includes congenital joint contractures, renal tubular dysfunction, cholestasis and early death. Additional features include ichthyosis, central nervous system malformations, platelet dysfunction, and severe failure to thrive. We studied three patients with cholestasis, increased aminotransferases, normal gamma-glutamyl transferase and developmental and language delay. Whole exome sequencing analysis identified VPS33B variants in all patients: patients 1 and 2 presented a novel homozygous variant at position c.1148T>A p.(Ile383Asn), and patient 3 was compound heterozygous for the same c.1148T>A variant, in addition to the c.940-2A>G variant. ARCS is compatible with the symptomatology presented by the studied patients. However, most patients that have been described in the literature with ARCS had severe failure to thrive and died in the first six months of life. The three patients studied here have a mild ARCS phenotype with prolonged survival. Consequently, we believe that the molecular analysis of the VPS33B and VIPAS39 should be considered in patients with normal gamma-glutamyl transferase cholestasis.